2000
DOI: 10.1007/pl00010350
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap Between Organisational Needs and ERP Functionality

Abstract: We argue that ERP installations are difficult to align to specific requirements of the enterprise because of the low level at which ERP functionality is described. We raise this level from a functional description to a goal-oriented one. We use SAP R/3 to illustrate this. A SAP goal expresses the task that a SAP function carries out and abstracts away from the performance of this task. Since a SAP goal can be achieved in many ways, we introduce the notion of SAP strategies. We organise goals and strategies as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
90
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 1 publication
(1 reference statement)
0
90
0
4
Order By: Relevance
“…They observe that the system frustrates the normal way of handling processes. Maybe the system is not able to support the process as it should be carried out, or maybe the business process as implemented in the enterprise information system is not known or accepted by the employees [30]. As a result, the actual business process may diverge from the processes as implemented in the enterprise information system.…”
Section: Introductionmentioning
confidence: 99%
“…They observe that the system frustrates the normal way of handling processes. Maybe the system is not able to support the process as it should be carried out, or maybe the business process as implemented in the enterprise information system is not known or accepted by the employees [30]. As a result, the actual business process may diverge from the processes as implemented in the enterprise information system.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in ERP RE has identified flaws with these standard processes and proposed creative solutions to reduce the cost of ERP RE by avoiding scope creep, involving the right stakeholders, allocating sufficient resources, and enlisting vendors' and consultants' support to RE problems [3,4,8,9,10,11,16,28,34]. Nevertheless, the central problem of ERP implementation still exists: to find a match between the flexibility often required by the business, and the rigidity usually imposed by the ERP system.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of non-alignment between business and technical requirements in design of enterprise business processes has been widely studied in the research community ( [2], [3], [4], [5], [6]). Our work differs in two aspects.…”
Section: Introductionmentioning
confidence: 99%